Sales Information System: A Case Study at an Indonesian Pharmaceutical Manufacturing - Bonfilio Wilson Atmadja; Raymond Sunardi Oetama (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
The effective design of information systems plays a crucial role in enhancing productivity and efficiency across various industries, particularly in the business sector. For numerous companies, integrating a comprehensive information system has become indispensable, effectively reducing risks such as human errors, fraud, and data inaccuracies. This study suggests developing a web-based information system specifically optimizing the sales process. The Rapid Application Development methodology has been chosen for system design to achieve this objective. This approach utilizes XAMPP as the web server, Visual Studio Code as the code editor, PHP as the programming language, CodeIgniter as the framework, and MySQL for the database. Implementing this information system offers several advantages for the organization, addressing current issues and enhancing operations. It streamlines the management of sales-related data by automating various processes. Additionally, the system simplifies the generation of crucial documents like sales reports, invoices, component selection, and delivery orders. These reports serve as invaluable resources for analysis and decision-making, empowering the company to plan and develop future business processes efficiently. The data reveals an impressive average user acceptance score of 97.1%, highlighting substantial user satisfaction and endorsement.